Assessment of Pre-Diabetes in Young Adults of Age 18-40yrs in Andhra University College of Pharmacy, Visakhapatnam - R. B, Veera; K, Alekhya.; D, Kavitha.; A, Annapurna. (Indian Journal of Pharmacy Practice)
The incidence of diabetes is continuously increasing worldwide. Pre-diabetes (defined as impaired glucose tolerance, impaired fasting glucose or both) represents an intermediate state, which often to overt diabetes within a few years. The aim of the study is to assess the pre-diabetes in the students and staff of University College of Pharmaceutical Sciences, Andhra University. Methods: Diagnosis of Pre-diabetes was based on WHO diagnostic criteria. A cross-sectional study was conducted for a period of 9 months. A total 245 volunteers were taken for the study between the age group of 20-40 years. Fasting plasma glucose and oral glucose tolerance test was done and samples were estimated for different risk factors. The data was collected and analyzed in percentage. Results: 38(15.4%) subjects were in pre-diabetes stage (Impaired fasting glucose 30 (12.2%), Impaired glucose tolerance 8(3.26%) and with both features 6(2.4%). Apart from the familial history, elevated triglycerides levels, BMI and decreased levels of HDL was found to be leading risk factors prevailing in the subjects studied (N = 245). Conclusion: 15.4% of the subjects were found to be prediabetic. All the pre-diabetics are identified as male subjects. It was found that in more than 50% of the subjects apart from family history, hypertriglyceridemia, BMI and low levels of HDLcholesterol were elevated.
Keywords: Pre-diabetes; impaired fasting glucose; oral glucose test; triglycerides